UTAUT Model: Identifying the Driving Factors of the Intention to Use Paylater - Pratika, Yeyen (Jurnal Bisnis dan Manajemen, 2021)
Information and Communication Technology (ICT) has developed rapidly that drives to the growth of digital transaction in recent years. E-commerce companies create features in order to deal with their customers, such as paylater in their digital payment. It offers a payment method that is almost similar to a credit card which allows customers to buy products or services right now with the delaying of payment. This phenomenon becomes regular in e-commerce business. Thus, this study aims to examine what factors influence individual behavioral intention in adopting paylater by using Unified Theory of Acceptance and Use of Technology (UTAUT) theory. A total of 167 respondents was involved in this study. Data were analyzed by using Structural Equation Modeling (SEM). The result showed that only performance expectancy and facilitating conditions have a significant influence on behavioral intention.